Umbilical Cord Coiling Index as A Marker of Perinatal Outcome: Umbilical Cord Coiling Index for Perinatal Outcome - Jan, Sadiq; Qamar, Ayesha; Javed, Muhammad Asif; Zulfiqar, Seharish; Jamil, Sara; Aziz, Moizza (Pakistan Journal of Health Sciences, 2024)
Umbilical cord coiling patterns have a considerable effect on both pregnancy outcomes and fetal health. Objectives: To assess the postnatal umbilical coiling index and investigate its association with normal coiling, hypo-coiling, and hyper-coiling patterns about maternal and perinatal outcomes. Methods: This cross-sectional study was conducted at the Obstetrics and Gynecology Department of Pakistan Aeronautical Complex Hospital Kamra from January 2024 to June 2024. The patterns of umbilical cord coiling were analyzed in 200 Livebirths. This study utilized convenience sampling to select a sample of live births for assessing the relationship between the umbilical cord coiling index and perinatal outcomes. Data were collected on maternal factors and neonatal outcomes, including Apgar scores. Statistical analysis was conducted using SPSS version 26.0, with descriptive statistics to summarize the data and inferential tests (e.g., chi-square test, t-test, regression analysis) to evaluate associations between umbilical cord coiling patterns and perinatal outcomes. Results: The study revealed that hypo-coiled cords were linked to older maternal age (≥35 years) and higher gestational diabetes rates. Hypo-coiled infants had a low birth weight incidence of 28.6%, significantly lower coiling index (0.07 ± 0.02), and lower Apgar scores at one minute (6.8 ± 1.2) and five minutes (8.2 ± 0.9). These results suggest umbilical cord coiling patterns are crucial indicators of maternal health and neonatal outcomes, highlighting the need for careful monitoring in at-risk pregnancies. Conclusions: It was concluded that there is a correlation between neonatal outcomes and factors such as maternal age, gestational diabetes, and abnormal umbilical cord coiling patterns.